Get With The Guidelines®–Stroke performance indicators in patients with transient ischemic attack - Lorena Souza Viana Schneider; Vinicius Boaratti Ciarlariello; Renata Carolina Acri Nunes Miranda; Andreia Heins Vaccari; Rodrigo Meirelles Massaud; Gisele Sampaio Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT Get With The Guidelines®–Stroke is an in-hospital program for improving stroke care by promoting adherence to scientific guidelines. Of the patients with transient ischemic attack (TIA), 10-15% have a stroke within three months, and many patients do not receive the recommended interventions to prevent this outcome. Objective: The goal of this study was to assess the adherence to stroke quality indicators in patients with TIA. Methods: This retrospective observational study evaluated consecutive patients admitted to a primary stroke center with TIA or acute ischemic stroke (AIS) from August 2008 to December 2013. Six quality indicators applicable to both TIA and AIS were analyzed and compared between groups. Results: A total of 357 patients with TIA and 787 patients with AIS were evaluated. Antithrombotic medication use within 48 hours of admission, discharge use of anticoagulation for atrial fibrillation and counseling for smoking cessation were similar between groups. In the TIA group, discharge use of antithrombotic medication (95% versus 98%; p = 0.01), lipid-lowering treatment (57.7% versus 64.1%; p < 0.01) and stroke education (56.5% versus 74.5%; p < 0.01) were all less frequently observed compared with patients with AIS. Conclusions: The adherence to some of the Get With The Guidelines®–Stroke quality indicators was lower in patients with TIA than in patients with AIS. Measures should be undertaken to reinforce the importance of such clinical interventions in patients with TIA.